Clinical efficacy of tetrandrine in artificial stone-associated silicosis: A retrospective cohort study - Wu, Wen-hong; Feng, Yong-hong; Min, Chun-yan; Zhou, Shao-wei; Chen, Zi-dan; Huang, Li-min; Yang, Wen-lan; Yang, Guang-hong; Li, Jun; Shi, Jin; Quan, Hua; Mao, Ling (Frontiers in Medicine, 2023)
Background: Outbreaks of silicosis have occurred among workers in the artificial stone (AS) industry, and there is currently no effective antifibrosis treatment for silicosis. Design: A retrospective cohort study Methods: We retrospectively analyzed the clinical data of 89 artificial stone-associated silicosis patients treated in Shanghai Pulmonary Hospital (China). Patients who agreed to be administered tetrandrine entered the observation group and those who disagreed entered the control group. Changes in chest HRCT, pulmonary function and clinical symptoms of patients in two groups were compared pre- and post-treatment. Results: After treatment for 3–12 months, 56.5%–65.4% of patients in the observation group showed improvements in HRCT imaging, while there was no improvement in the control group (P＜0.05). Disease progression occurred in 0%–17.4% of patients in the observation group after 3–12 months of treatment compared with 44.4%–92.0% of patients in the control group (P < 0.05). After 3 months of treatment, the forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1) and diffusing capacity of the lung for carbon monoxide (DLco) in the observation group increased by 136.7±189.2 ml (P＜0.05), 124.2±169.9 ml (P＜0.05) and 1.4±2.3 ml/min/mmHg (P > 0.05), respectively, while those in the control group decreased (145.8±356.5; 107.5±272.1; 1.9±3.8). After 6 months of treatment, FVC, FEV1 and DLco in the observation group increased by 207.8±372.2 ml (P> 0.05), 107.8±295.2 ml (P> 0.05) and 0.7±6.0 ml/min/mmHg (P > 0.05), respectively, while those of the control group decreased (383.3±536.7; 215.6±228.9; 1.4±1.7). The incidences of clinical symptoms such as cough, expectoration, dyspnea, chest tightness and chest pain in the observation group were decreased-after treatment (all P < 0.05), while the incidences of these symptoms increased in the control group, although the change was not statistically significant (all P > 0.05). Conclusion: Tetrandrine can control and delay the progression of AS-associated silicosis fibrosis, with improved chest HRCT imaging and pulmonary function.